Syntax of Dutch: Verb and Verb Phrases. Volume 2 - Corver, Norbert (Comprehensive Grammar Resources, 2015)
Syntax of Dutch: Verbs and Verb Phrases consists of three volumes. Volume 1 opens with a general introduction to verbs, including a review of various verb classifications and discussions on inflection, tense, mood, modality and aspect. This is followed by a comprehensive discussion of complementation (argument structure and verb frame alternations). Volume 2 continues the discussion of complementation, but is more specifically focused on clausal complements: the reader will find detailed discussions of finite and infinitival argument clauses, complex verb constructions and verb clustering. Volume 3 concludes with a description of adverbial modification and the overall structure of clauses in relation to, e.g., word order (verb placement, wh-movement. extraposition phenomena, scrambling, etc.).